Bilateral Osteotomy of Pedicles for En Bloc Resection of a Malignant Tumor of the Posterior Thoracic Spine: A Case Report. Issue 3 (13th July 2022) - Aibara, Noriyuki; Watanabe, Kota; Asano, Naofumi; Suzuki, Satoshi; Takahashi, Yohei; Nori, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Yagi, Mitsuru; Nakamura, Masaya; Matsumoto, Morio
Abstract : Case: A 45-year-old woman had a grade II chondrosarcoma (T2N0M0G2) located at the spinous processes and laminas of T3-6 with the tumor extension into the spinal canal at T3-4. To perform en bloc tumor resection, we released or disarticulated bilateral costovertebral ligaments from T3-6 and cut the bilateral pedicles at T3-5 all from posteriorly. Then, we completed en bloc resection without violating the tumor capsule. Conclusion: Our novel procedure, bilateral osteotomy of pedicles for en bloc resection successfully allowed for en bloc tumor resection involving the posterior elements with wide surgical margins.